Scalability and Interoperability Challenges in the Web 3.0 Ecosystem - Prajapati, Prince Kumar; Sinha, Amit Kumar (Journal of Research in Science and Engineering, 2025)
Web 3.0 promises a decentralized and user - empowered internet built on blockchain technology. However, significant challenges in scalability and interoperability threaten to impede its widespread adoption. This paper explores the current state of these challenges and their impact on Web 3.0's development. We examine the limitations of existing blockchain solutions in handling high transaction volumes and discuss the hurdles hindering seamless communication between different blockchain networks. Furthermore, we analyze the importance of addressing these issues to unlock the full potential of Web 3.0, fostering a more secure, transparent, and user - controlled online experience.